Monosodium Urate Crystal Deposition in Coronary Artery Plaque by 128-Slice Dual-Energy Computed Tomography: An Ex Vivo Phantom and In Vivo Study. Issue 6 (1st November 2021) - Feuchtner, Gudrun M.; Plank, Fabian; Beyer, Christoph; Schwabl, Christoph; Held, Julia; Bellmann-Weiler, Rosa; Weiss, Guenther; Gruber, Johann; Widmann, Gerlig; Klauser, Andrea S.
Abstract : Objective: Monosodium uric acid (MSU) crystals may accumulate in the coronary plaque. The objective was to assess whether dual-energy computed tomography (DECT) allows for detection of MSU in coronary plaque. Methods: Patients were examined with 128-slice DECT applying a cardiac electrocardiogram-gated and peripheral extremity protocol. Patients were divided into 3 groups: gout (tophi >1 cm in peripheral joints), hyperuricemia (>6.5 mg/dL serum uric acid), and controls. The groups were matched for cardiovascular risk factors. Monosodium uric acid–positive (+) and calcified plaque were distinguished, and the coronary artery calcium score was calculated. Ex vivo phantom: MSU solutions were diluted in different NaCL solutions (5%/10%/15%/20%/25%). Coronary artery models with 2 different plaque types (MSU+ and calcified) were created. Results: A total of 96 patients were included (37 with gout, 33 with hyperuricemia, and 26 controls). Monosodium uric acid–positive plaques were found more often in patients with gout as compared with controls (91.9% vs 0.38%; P < 0.0001), and the number of plaques was higher ( P < 0.0001). Of 102 MSU+ plaques, 26.7% were only MSU+ and 74.2% were mixed MSU+/calcified. Monosodium uric acid–positive plaque had mean 232.3 Hounsfield units (range, 213–264). Coronary artery calcium score was higher in patients with gout as compared with controls (659.1 vs 112.4 Agatston score; P < 0.001). Patients with gout had more MSU+ plaques as compared with patients with hyperuricemia (91.6% vs 2.9%; P < 0.0001), and coronary artery calcium score was higher (659.1 vs 254 Agatston score; P < 0.001), but there was no difference between patients with hyperuricemia and controls. Ex vivo phantom study: MSU crystals were detected by DECT in solutions with a concentration of 15% or greater MSU and could be distinguished from calcified. Conclusions: Coronary MSU+ plaques can be detected by DECT in patients with gout.